NMO in pediatric patients: brain involvement and clinical expression - Joaquín A. Peña; María Elena Ravelo; Eduardo Mora-La Cruz; Cecilia Montiel-Nava (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To analyze the clinical, neuroimaging characteristics and positivity of the acquaporin water channel (NMO-IgG) in pediatric patients with neuromyelitis optica (NMO). This disorder could have a variable clinical expression. To address such variability, the term NMO spectrum has been suggested. METHOD: We evaluated six pediatric patients, with a median age of 11 years at the time of the study, with the diagnosis of NMO by the Wingerchuck criteria. RESULTS: All the cases exhibited bilateral optic neuritis (ON). Four patients had abnormalities on brain MRI from the onset,although only three of them developed symptoms correlated to those lesions during the course of their disorder. NMO-IgG was positive in 80%. CONCLUSION: Optic neuropathy is the most impaired feature in NMO patients. Brain MRI lesions are not compatible with multiple sclerosis and positivity of the NMO-IgG are also present in NMO pediatric patients, confirming the heterogeneity in the expression of this disorder.